2010
DOI: 10.1007/s10763-010-9217-4
|View full text |Cite
|
Sign up to set email alerts
|

Promoting an Inclusive Image of Scientists Among Students: Towards Research Evidence-Based Practice

Abstract: This study aims at investigating the effects of a teaching intervention, the design of which is informed by evidence from educational theories and research data, on students' images of scientists. A quasi-experimental design with a non-equivalent pre-test-post-test control group (CG) was used to compare the outcomes of the intervention. The subjects of the study were 63 grade 6 (aged 12 and 13) students who were in two different classes and taught by two different teachers. The study was undertaken in ten clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 39 publications
1
15
1
1
Order By: Relevance
“…Los autores afirman además que esa no es la única forma de llevar los científicos al aula, sino que existen diversas formas de hacerlo, como por ejemplo a través del correo electrónico, las conferencias virtuales, etc., como también la oportunidad de hacer visitas a los laboratorios y lugares de trabajo. Cakmakci et al (2011) sostienen asimismo que tanto los resultados de la investigación empírica sobre la imagen de científico de los estudiantes como también los estudios teórico-analíticos acerca de la naturaleza del conocimiento, el pensamiento, el aprendizaje y la enseñanza, Las imágenes inadecuadas de ciencia y de científico... pueden usarse para diseñar actividades de enseñanza destinadas a mejorar las ideas de las y los estudiantes acerca de la ciencia y los científicos. Coinciden en señalar que en general estas estrategias no son lo suficientemente utilizadas o bien se aplican muy tarde.…”
Section: En Procura Del Cambiounclassified
“…Los autores afirman además que esa no es la única forma de llevar los científicos al aula, sino que existen diversas formas de hacerlo, como por ejemplo a través del correo electrónico, las conferencias virtuales, etc., como también la oportunidad de hacer visitas a los laboratorios y lugares de trabajo. Cakmakci et al (2011) sostienen asimismo que tanto los resultados de la investigación empírica sobre la imagen de científico de los estudiantes como también los estudios teórico-analíticos acerca de la naturaleza del conocimiento, el pensamiento, el aprendizaje y la enseñanza, Las imágenes inadecuadas de ciencia y de científico... pueden usarse para diseñar actividades de enseñanza destinadas a mejorar las ideas de las y los estudiantes acerca de la ciencia y los científicos. Coinciden en señalar que en general estas estrategias no son lo suficientemente utilizadas o bien se aplican muy tarde.…”
Section: En Procura Del Cambiounclassified
“…Culture: The DAST has been used by researchers in a number of different countries, including Bolivia and Columbia (Medina-Jerez, Middleton, & Orihuela-Rabaza, 2010), Hong Kong (Fung, 2002), Italy (Manzoli et al, 2006), and Turkey (Cakmakci, Tosun, Turgut, Orenler, Sengul, & Top, 2011). Some multinational studies have also utilized the DAST to examine the influence of culture upon perceptions of scientists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have indicated that children's perceptions of scientists are malleable and that they can be changed by interventions such as having female scientists as classroom visitors, using gender-balanced materials, providing opportunities for informal interactions with scientists, and incorporating hands-on inquiry activities (e.g., Finson, 2009;Minogue, 2010;Moseley, & Norris, 1999). For example, in a quasi-experimental study of 63 Grade 6 Turkish students changes were found in images of scientists after evidence-informed constructivist approaches to instruction that emphasized discussion and reflection were implemented (Cakmakci et al, 2011). Huber and Burton (1995) found that after a semester of hands-on science activities, boys' drawings of scientists became less stereotypic.…”
Section: Insert Figure 2 Herementioning
confidence: 99%
“…Lines of research that provided evidence for activities that effect student's attitudes towards the image of the scientist and could improve it, were adopted here to make the set of interventions that were used. Insights were drawn from research on students at varying ages, about the image of scientists and interventions that changed it [3,5,6,13,14,15]. Intervention was reinforced by the use of conflict situations following the social constructivism [16].…”
Section: Model For Conceptual Changementioning
confidence: 99%